Model Pengembangan Sistem Informasi Akademik Berbasis User Centered Design Menerapkan Framework Flask Python - Ngantung, Ronaldo Kristoforus; Pakereng, M A Ineke (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Along with the rapid development of the times, one of which is in the field of information technology, this is increasingly demanding that we have to work faster. The ineffective technological development at SMK Negeri 1 Bitung makes students and teachers still using the manual system in academic activities, such as inputting grades, in providing information on school activities and so on. SMK 1 Negeri Bitung needs technology development solutions as school infrastructure. In this study, an Academic Information System was designed by implementing the Flask Python Framework technology. This study shows the performance of the system to help the process of academic activities to be better